Resonant effects in the strongly driven phase-biased Cooper-pair box - Shevchenko, S.N.; Omelyanchouk, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We study the time-averaged upper level occupation probability in a strongly driven two-level system, particularly its dependence on the driving amplitude x0 and frequency w and the energy level separation DE. In contrast to the case of weak driving (x0 << D E), when the positions of theresonances almost do not depend on x0, in the case of the strong driving (x0 ~ D E) their positions are strongly amplitude dependent. We study these resonances in the concrete system — the strongly driven phase-biased Cooper-pair box, which is considered to be weakly coupled to the tank circuit.